2022
DOI: 10.1097/prs.0000000000009733
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Assess Effectiveness and Safety of a Hyaluronic Acid Filler for Chin Augmentation and Correction of Chin Retrusion

Abstract: Background: The chin is important for facial appearance, affecting overall balance and harmony of the face. The purpose of this study was to evaluate effectiveness of the hyaluronic acid filler Restylane Defyne for chin augmentation and correction of chin retrusion versus a no-treatment control. Methods: Male and female subjects, aged 22 years or older, with mild to moderate chin retrusion, were randomized 3:1 to the hyaluronic acid filler Restylane Defyne (n = 107) or no treatment (n = 33). Assessments incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The endpoints and definitions used were comparable to our study (i.e., GCRS responder rate was also ≥ 1-grade improvement). In terms of baseline severity, Marcus et al [ 5 ] presented that 63% of patients in the HA DEF group in the US study had moderate retrusion, which was comparable to 65% in this study (Table 1 ).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The endpoints and definitions used were comparable to our study (i.e., GCRS responder rate was also ≥ 1-grade improvement). In terms of baseline severity, Marcus et al [ 5 ] presented that 63% of patients in the HA DEF group in the US study had moderate retrusion, which was comparable to 65% in this study (Table 1 ).…”
Section: Discussionsupporting
confidence: 72%
“…The assessment scale used to measure chin retrusion in this study was the validated 4-point GCRS designed to measure a clinically relevant improvement. This scale has also been used in a previous US study (Marcus et al ) [ 5 ] using the same HA product, HA DEF , and was therefore considered the most appropriate choice for confirming the effectiveness in this additional population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, hardly any RCTs or CTs that focused on the chin or glabella region could not be found that met our inclusion criteria; these facial areas were thus not included due to limited data. The RCTs that did include the chin or glabella region did not report the same adverse events as our included studies, thus would not allow us to run an effective analysis [ 54 - 55 ].…”
Section: Reviewmentioning
confidence: 99%